The gut microbiota and mental health - Moqbil, Sara; Niedobylski, Sylwiusz; Laszczak, Katarzyna; Warchoł, Konrad; Mikos, Eryk (Journal of Education, Health and Sport, 2021)
INTRODUCTION AND PURPOSE Recent studies have shown that changes in the microbiome, probiotic and antibiotic supplementation, can significantly modulate various forms of neuropsychiatric disorders - such as depression, anxiety and stress-related disorders. There is growing body of evidence pointing to a bidirectional correlation along the brain-gut microbiota line. This axis is connected through endocrine, immune and neuronal pathways. The nerves that make up the enteric nervous system transmit modifications occurring in the gastrointestinal tract and through the vagus nerve to the central nervous system (1). The main purpose of this review is to update recent information on the correlation between the gut microbiota and mental health. STATE OF KNOWLEDGE Interactions between the gastrointestinal system and brain function have become an important field of psychiatric research in recent years. Probiotics are thought to be a potentially valuable player in the treatment of many neuropsychiatric disorders. However, the role of specific gut microbiota species in the development of these disorders remains unclear. CONCLUSIONS Increasing knowledge of the correlation between gut microbiota and mental health may improve the quality of treatment for patients with neuropsychiatric conditions. Further research on larger groups is needed to assess whether probiotics can modify altered psychological well-being and be integrated into current, conventional treatments.